(untitled) (Scottish Historical and Archaeological Internet Reports, 2013)
Key among the discoveries are the boundary features of the burgh, including an early ditch. The identified sequence of boundaries at Holyrood Road saw the Canongate Ditch superceded by a 13th-14th century palisade and then in turn by an early 16th century wall.